2022
DOI: 10.1186/s40066-022-00397-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying “local food” online and social media in the United States for 2018–2021

Abstract: Background Interest in local food has been growing, driven by increased attention from consumers, supporting policies, and interest in offering supply by local producers. Nonetheless, a definition of “local food” remains elusive, varying with purposes, geographies, and perceptions. This study quantifies online media mentioning local food in 2018–2021 using online and social media listening and analytics. In addition, a sub-search devoted to local food security and access was conducted due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Although this study examined food security more broadly, sentiment analysis has also been used to investigate specific areas of food security. For example, a study assessing the sentiment of web-based conversations specifically related to local food and food banks found that the net sentiment was negative [82]. In contrast, the Twitter posts in this study classified in topics related to food banks were largely positive.…”
Section: Comparison With Prior Workcontrasting
confidence: 54%
See 1 more Smart Citation
“…Although this study examined food security more broadly, sentiment analysis has also been used to investigate specific areas of food security. For example, a study assessing the sentiment of web-based conversations specifically related to local food and food banks found that the net sentiment was negative [82]. In contrast, the Twitter posts in this study classified in topics related to food banks were largely positive.…”
Section: Comparison With Prior Workcontrasting
confidence: 54%
“…In contrast, the Twitter posts in this study classified in topics related to food banks were largely positive. This is likely due to the type of discussion in the study by Jung et al [82] being dominated by negative words such as "struggle," "difficult," and "desperate," whereas this study discussed more positive aspects, such as donations, support of food banks, and having access to these services. In addition, Scott et al [83] examined the Supplemental Nutrition Assistance Program (SNAP) in the United States.…”
Section: Comparison With Prior Workmentioning
confidence: 66%
“…Thus, providing a quality e-grocery service is vital for e-grocery businesses. Throughout the COVID-19 pandemic, to prevent the spread of disease, online services became important systems to limit the physical interaction between food customers and retailers (Jung et al, 2022). Past studies in e-commerce reveal that if customers perceive that the e-service is reliable and trustworthy, their perception of the e-service will be stronger, subsequently influencing their preference and intention to repeat the experience (Lopez et al, 2018;Soni and Vohra, 2022):…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Recent research in e-commerce shows that e-grocery is a popular method for purchasing groceries. Throughout the COVID-19 pandemic, this purchasing medium became a preferred method for purchasing groceries as it posed a lower health risk compared to visiting retailers (Fetriyuna, 2022; Jung et al , 2022; Zhang et al , 2022). As a consequence, the e-grocery business has attracted many business players causing intense competition (Cappelli et al , 2022; Ferguson and Thompson, 2021).…”
Section: Introductionmentioning
confidence: 99%